Vine mealybug, Planococcus ficus (Signoret) (Hemiptera: Pseudococcidae ), a Key Pest in South African vineyards. A Review - Walton, V.M.; Pringle, K.L. (South African Journal of Enology and Viticulture, 2017)
Vine mealybug, Planococcus ficus (Signoret), is a key pest in vineyards in the Western Cape and North-West Provinces of South Africa and more recently in the USA. This pest was first reported in the Western Cape Province in 1943. The taxonomy and identification of this species are made difficult by complex slide-mounting techniques and the lack of qualitative characteristics. Vine mealybug is polyphagous with a wide range of host plants. P. ficus causes direct crop loss due to desiccation of bunches in the case of wine grapes and unsightly honeydew excretion on bunches in the case of table grapes. High infestations of P. ficus can cause early leaf loss and resultant weakening of vines. Vine mealybug also vectors the vine leafroll virus. This pest is currently controlled using chemical, biological and cultural control techniques in an integrated pest-management system. This system relies on the use of pheromone and physical monitoring techniques, which provide information on infestation levels.